A Kantian evaluation of Taylorism in the workplace - Green, Michael K. (Journal of business ethics, 1986)
A Kantian evaluation of Taylorism in the workplace requires a consideration of four problems; (1) the conditions of agency, (2) the relation of Taylorism to these conditions, (3) an explanation of the method given by the Typic for applying the Categorical Imperative, and (4) the actual application of the Categorical Imperative to Taylorism. An agent who views himself as a performer is distinguished from an agent who is a mere observer of his own actions, and it is argued that Taylorism in effect attempts to remove the purposiveness of action from the workmen and to reduce them to the state of being mere observers of their own actions. Then it is argued that in order for one to attempt to think of a maxim as a universal law, one must posit a universal and necessary connection between the circumstances and the performances and then another such connection between the action and the purpose to be achieved. A model is constructed using heat-seeking machines, and it is argued that a principle analogous to Taylorism could not hold as a universal law for such machines. Thus, Taylorism is not an acceptable solution to the problem of coordinating the activities of self-directed agents within the workplace.